A Framework to Improve Customer Service Using Brahms Model - Abid Ghaffar; Mohamed Ridza Wahiddin; Mohamad Fauzan Noordin; Asadullah Shaikh (Timeline Publication Pvt. Ltd., 2024)
Human behaviour plays a vital role in the success and failure of an organization. Top management set organizational goals and objectives to run their business activities. Skill sets, proper training, team work, commitment, infrastructure and resources bring vital changes in any work practice system. The great challenge is to detect human behavioural errors while performing job activities in the customer service department of an organization. Human behavioural errors in the work practice system is a key factor to change the whole scenario. These errors could be monitored and well detected using a framework comprised of Brahms Model and Warning Alert Generation System. Rapid action and response from the management team can be established by using the same framework. Efficiency and quality assurance for the customer service improvement in an organization could be guaranteed and maximized.